Walk This Way, Gait Training with Rhythmic Auditory Stimulation for a Veteran with a Transtibial Amputation. - Penny, Jamie Wollenberg; Evans, Estey; Martin, Julie (Orthopedic Physical Therapy Practice, 2025)
Background and Purpose: Asymmetry in spatiotemporal gait parameters is commonly observed in individuals following transtibial amputation (TTA). Evidence exists supporting Rhythmic Auditory Stimulation (RAS) during gait training for patients with neurological deficits, but limited research is available for patients with a TTA. The purpose of this case report is to determine if the spatiotemporal parameters of gait and functional mobility for a Veteran with a TTA would be influenced by the inclusion of RAS gait training within a physical therapy plan of care. Methods: A 60-year-old Veteran, 9 months status-post TTA participated in physical therapy that included 20 minutes of gait training with RAS, twice weekly for 4 weeks. Clinical Findings: Clinically significant improvements were observed on step length, step width, and safe community ambulation with a prosthesis. Clinical Relevance: Rhythmic Auditory Stimulation is a low-risk, easily accessible, cost-effective supplement for gait training patients with TTA. Conclusion: Gait training with RAS improved spatiotemporal gait parameters, increased gait speed, improved aerobic capacity, and reduced risk of falls in this Veteran.